PENGARUH MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN - Rendy Marasabessy (Jurnal Cakrawala Ilmiah, 2025)
This research aims to explore the influence of social media on consumer purchasing decisions by taking into account psychological, social, and marketing strategy factors adopted by businesses. In the current digital age, social media has emerged as a highly effective marketing tool, shaping consumer behavior and preferences through various approaches, including influencer endorsements, paid advertisements, and user-generated content. By employing a quantitative approach and survey method, this study gathered data from respondents aged 18 to 35 who are active social media users. The findings reveal that social media significantly impacts consumer purchasing decisions, influenced by factors such as trust in influencers, product reviews from other users, and the effectiveness of digital advertising. Moreover, e-commerce features integrated into social media platforms simplify transactions and enhance consumer purchase interest. The results of this research highlight that social media is not merely a communication platform but also plays a vital role in shaping contemporary consumer behavior. Thus, gaining deeper insights into the role of social media in purchasing decisions can assist businesses in crafting more effective marketing strategies while enabling consumers to make more informed and rational buying choices